Contribution of snow water equivalent to the terrestrial water storage changes in High Mountain Asia based on multiple datasets - Qian Li; Weili Duan; Tao Yang; Yuting Fan; Lanhai Li (Journal of Hydrology: Regional Studies)
Study region: High Mountain Asia. Study focus: Snow water equivalent (SWE) storage is a crucial component of the terrestrial water storage (TWS) in High Mountain Asia (HMA). This study employed monthly data from the Global Land Data Assimilation System (GLDAS) NOAH, GLDAS catchment land surface model (CLSM), European Centre for Medium Range Weather Forecasts reanalysis version 5 land (ERA5L), High Asia refined analysis (HAR), and the China Meteorological Administration’s global Land surface reanalysis Interim (CRA) during 2003–2020 to compare the TWS anomaly (TWSA). Additionally, the contribution of SWE to the TWS changes was estimated. New hydrological insights for the region: The results reveal that the TWSA had a large variability for the multiple datasets while the SWE anomaly (SWEA) time series exhibited more consistent fluctuations. The annual percentage of the SWEA to the TWSA ranged between 7.40–26.95 % for the multiple datasets, indicating the relatively important role of the SWE dynamics in the study area. Three main types of contributions were found in HMA, i.e., positive contributions when the TWSA and SWEA both decreased or both increased, and a negative contribution when the SWEA increased and the TWSA decreased. The individual role of the SWEA in controlling the total TWSA showed large regional and seasonal heterogeneity. The results of this study provide an essential reference for water management and availability to large downstream population.